The Oxford handbook of the cognitive science of religion - Barrett, Justin L. 1971- (New York, NY Oxford University Press, 2022)
"Over time, more psychologists have become contributors to cognitive science of religion (CSR), but when are they doing CSR and when are they doing psychology of religion? Does it matter? In this chapter, contemporary scientific reflections on notions of death and the afterlife are sketched to illustrate the subtle differences between CSR and psychology of religion. These kindred scientific approaches overlap considerably, but attention to their central differences will assist scholars in finding complementarity, thereby improving both schools of inquiry and their contributions to each other. After developing this thesis, this chapter introduces the organization and flow of the volume as a whole. Beginning with general theoretical and methodological foundations, the volume then considers specific applications of CSR to substantive topics such as beliefs in gods, sacred texts, sacred objects, and ritualized behaviors, before turning to how these domains of cultural expression are sometimes joined (or not) into religious systems. The volume ends with comparisons between CSR and two other neighboring approaches (evolutionary studies of religion and neuroscience of religion) and, finally, implications of CSR for philosophy of religion, religious education, and theology"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Psychology and religion; Psychology, Religious; Cognitive Science